1996
DOI: 10.1103/physrevb.53.9626
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure ofCuV2S4

Abstract: The results of ab initio band-structure calculations and measurements of x-ray-emission valence spectra ͑XES͒ ͑Cu L␣, V K␤ 5 , V L␣, S K␤ 1,3 , S L 2,3 ) and x-ray-photoelectron valence-band and core-level spectra ͑XPS͒ of CuV 2 S 4 thiospinel are presented. It is found that a peak in valence-conduction bands close to Fermi level is formed by V 3d states, which provide the metallic properties of CuV 2 S 4 . The valence band is formed by Cu 3d, V 3d, V 4p, and S 3p states. Examination of the XES and XPS results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
15
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…12 from that reported in [1,3,4,6]. The latter data had a sharp decrease at 90 K. The sin- gle crystal and the fine powders used in the present investigations were grown by Nagata's group, who already reported the important magnetic, electric, and thermal properties of CuV 2 S 4 [7,8,10,11,15,16]. At the moment, it is not easy for us to explain the origin of the difference, though we think that the results depend on the type of specimen used -one single crystal, single crystals, polycrystalline fine powders, and polycrystals -in addition to the instrumental condition of the measurements, because the susceptibility depends on correlation between the crystallographic orientation of the specimen used and the direction and strength of the applied magnetic field.…”
Section: (C)supporting
confidence: 52%
See 1 more Smart Citation
“…12 from that reported in [1,3,4,6]. The latter data had a sharp decrease at 90 K. The sin- gle crystal and the fine powders used in the present investigations were grown by Nagata's group, who already reported the important magnetic, electric, and thermal properties of CuV 2 S 4 [7,8,10,11,15,16]. At the moment, it is not easy for us to explain the origin of the difference, though we think that the results depend on the type of specimen used -one single crystal, single crystals, polycrystalline fine powders, and polycrystals -in addition to the instrumental condition of the measurements, because the susceptibility depends on correlation between the crystallographic orientation of the specimen used and the direction and strength of the applied magnetic field.…”
Section: (C)supporting
confidence: 52%
“…After the CDW interpretations of the structural, electric, and magnetic anomalies [1], many investigations were carried out of the structural, magnetic, and electric properties of CuV 2 S 4 in the low-temperature region by means of X-ray diffraction [2][3][4][5], magnetic susceptibility [2,3,[5][6][7], electrical resistivity [2,5,[7][8][9][10], and NMR [4][5][6][11][12][13][14], in addition to the electronic density of states (DOS) [15][16][17]. Lu et al [15] argued using X-ray photoemission and X-ray spectroscopy that Cu ions are in the mono-valent state in Structural and magnetic properties of the spinel CuV 2 S 4 have been studied by means of X-ray diffraction using synchrotron radiation and measurements of magnetic susceptibility. The structural phase transitions occur at about 55 K and 90 K, and the superlattice reflections (h ± q o , k ± q o , l) having an orthorhombic reduced wavevector q o = (1/4, 1/4, 0) are observed at 10 K. This suggests that the structure below 55 K is a commensurate unit cell of 4a p × 4b p × c p , where the subscript 'p' means a pseudo-spinel structure, and that the structural phase transitions are induced by the cooperative displacement of S ions in one-dimensional VS 6 octahedral chains, which are aligned along an orthorhombic [110] direction.…”
mentioning
confidence: 99%
“…The oxidation state of Cu atoms of CuV 2 S 4 is closer to Cu + [22]. The bands near E F are predominantly of V 3d character, so that the metallic nature of CuV 2 S 4 comes mainly from the V atom [22]. The CDW-type phase transition can be suppressed by the random occupation of the octahedral sites in the spinel structure.…”
mentioning
confidence: 87%
“…Thus, we consider that a spatial distribution of V-3d orbitals is sensitive to the polarization of the incident X-ray. Lu et al [14] argued using X-ray photoemission and X-ray spectroscopy that Cu ions are in the monovalent state in CuV 2 S 4 . However, their calculated partial DOS suggested that there is a strong hybridization between V-3d and S-3p bands and between Cu-3d and S-3p bands.…”
Section: Discussionmentioning
confidence: 99%
“…Fleming et al [2] reported that CuV 2 S 4 exhibits modulation at 50 and 90 K in the magnetic susceptibility and the electrical resistivity, and that the modulation are related to the charge-density wave (CDW) structure having the reduced wavevector q = (1/3−δ, 1/3−δ, 0) below 50 K and q = (1/4−δ, 1/4−δ, 0) in the region of 50 to 90 K. The δ value is locked in the commensurate q = (1/4, 1/4, 0) at 75 K. After their reports for CDW, many investigations had been made of the structural, magnetic, and electric transitions at about 50, 75 and 90 K by X-ray diffraction [1−5], magnetic susceptibility [1−3, 5, 6], electrical resistivity [1, 2, 5−9], NMR [4, 5, 10−13]. Lu et al [14] argued using X-ray photoemission and X-ray spectroscopy that Cu ions are in the monovalent state in CuV 2 S 4 . They also reported the band states with the first-principles calculation.…”
Section: Introductionmentioning
confidence: 99%